Determination Of Zinc Species Using Ultrafiltration And Different Solid Sorbents. - Suitcharit, Charuwan; Mohamed, Norita; Lim, Poh Eng; Sirinawin, Warapom (Ivan Franko National University of L'viv., 2005)
A method or the determination of operationally-defined metal species at natural concentration levels has been developed. The method is based on a combination of physical characterization by size fractionation using ultrafiltration and chemical characterization by retention studies on different solid sorbents.